PRIVATE CLOUD STORAGE IN RURAL'S MANAGEMENT AND INFORMATION SYSTEM USING ROADMAP FOR CLOUD COMPUTING ADOPTION (ROCCA) - Muhammad Agreindra Helmiawan; Irfan Fadil (Universitas Maso'em Bandung, 2020)
The draft Management Policy and Rural Information system are all articles with several articles governing all information security. In concerning Business Continuity Management it is written